2014
DOI: 10.2224/sbp.2014.42.5.705
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Power Distance, Collectivism, Punishment, and Acquiescent, Defensive, or Prosocial Silence

Abstract: We investigated the relationships among power distance, collectivism, punishment, and a multidimensional construct of silence. Participants were 628 full-time employees of 27 heavy-industry companies in South Korea. Confirmatory factor analysis and structural equation modeling were performed to test our hypothesized model. The results revealed that power distance induced acquiescent silence; however, power distance did not have any impact on defensive silence. Collectivism also generated acquiescent silence bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 30 publications
2
41
1
5
Order By: Relevance
“…This subordinates behave passively and conceal their work-related concerns. This finding is in line with that of Rhee et al (2014), who found that disengagement finding is in line with that of Rhee et al (2014), who found that disengagement from decision making led individuals to behave passively and not give voice from decision making led individuals to behave passively and not give voice to their suggestions and opinions. However, we found that centralization did to their suggestions and opinions.…”
Section: Discussion Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This subordinates behave passively and conceal their work-related concerns. This finding is in line with that of Rhee et al (2014), who found that disengagement finding is in line with that of Rhee et al (2014), who found that disengagement from decision making led individuals to behave passively and not give voice from decision making led individuals to behave passively and not give voice to their suggestions and opinions. However, we found that centralization did to their suggestions and opinions.…”
Section: Discussion Discussionsupporting
confidence: 91%
“…Because it has been found that age and gender have a Because it has been found that age and gender have a potential impact on information sharing, previous researchers have controlled potential impact on information sharing, previous researchers have controlled for these demographic variables (Rhee et al, 2014;Wang & Hsieh, 2013). Thus, for these demographic variables (Rhee et al, 2014;Wang & Hsieh, 2013). Thus, we also controlled for age and gender of individuals by utilizing a close-ended we also controlled for age and gender of individuals by utilizing a close-ended format.…”
Section: Control Variablesmentioning
confidence: 99%
“…This may include additional communication and support from managers to enhance the perception that discussing problems and controversial topics is encouraged and emphasizing that no sanctions will be taken against employees that speak up on sensitive issues (e.g. Borins 2001; Axtell et al 2000;Premeaux and Bedeian 2003;Rhee, Dedahanov, and Lee 2014). In particular in cases where remaining silent could have strong detrimental consequences, this may include various procedures to safely or anonymously report issues, including the introduction of Ombudsmen and appropriate whistleblowing channels and safeguards.…”
Section: Discussionmentioning
confidence: 99%
“…Such fear is likely caused by a variety of factors. Not only can a message itself be controversial or potentially damaging, an employee's relationship with his/her supervisors and risks of being sanctioned are also likely determinants of an individual's inclination towards a defensive silence strategy (Vakola and Bouradas 2005;Wang and Hsieh 2013;Bommer and Jalajas 1999;Rhee, Dedahanov, and Lee 2014). Power asymmetries and perceptions thereof play an important role in this regard, as individuals with less power require the resources and support of their superiors, ensuring that the former will be sensitive to the latter's signals (Kiewitz et al 2016).…”
Section: Defensive Silencementioning
confidence: 99%
“…Dorfman y Howell (1988) extendieron el potencial del modelo, que consideraba la cultura como un atributo de la sociedad, al proponer escalas que permitieron medirla como un atributo individual, entendido como la fuerza de la creencia de un individuo en valores culturales clave. Su instrumento ha sido utilizado frecuentemente considerando las limitaciones psicométricas de las escalas originales, como por ejemplo que el índice de evitación de la incertidumbre se construyó con elementos que reflejan tres constructos diferentes (Daly, OwyarHosseiniand, & Alloughan, 2014;Fernandez et al,1997;Rhee, Dedahanov, & Lee, 2014).…”
Section: Alcances E Impacto Del Modelo De Hofstedeunclassified